The distributional effect of a large rice price increase on welfare and poverty in Bangladesh1. (4th March 2016) - Hasan, Syed A.
Abstract : This paper studies the distributional effect of a sharp rice price increase on welfare and poverty in Bangladesh. We employ household consumption data and include the indirect effect of price responses to estimate the welfare loss. Our findings suggest that the estimated welfare effect can be misleading if household responses to rice consumption and production are ignored. This study further supports the hypothesis that the poor are the main victims of such a shock. Our examination also indicates that a higher rice price may increase or decrease the poverty head‐count ratio, depending on the choice of the poverty line, but worsens the country's poverty situation when it is measured by the per capita consumption gap. Our analysis reveals that the government can play a central role to prevent and mitigate such shocks, particularly in the medium to long run. On the methodological side, we observe that consumption provides a more consistent outcome across different methods of analysis than household income.